Globalization and regional consumption disparity in China: A disaggregated analysis - Ul-Haq, Jabbar; Visas, Hubert; Hye, Qazi Muhammad Adnan; Sam, NGOH Christopher; Hameed, Kainat (Asian Development Policy Review, 2023)
Developing countries are increasingly concerned about globalization's impact on regional disparities. This paper looks at the relationship between globalization and regional (rural-urban) differences in consumption in China. It does this by separating globalization into the trade of domestic-invested enterprises (DIEs) and the trade of foreign-invested enterprises (FIEs). Feasible generalized least square (FGLS) is used for empirical analysis based on panel diagnostics. For the robustness of the findings, we also employed panel-corrected standard errors (PCSE) model. The results show a reduction in China's regional (i.e., urban-rural) consumption disparity (RCD) caused by both DIEs and FIEs trade perspectives. The impact of FIEs trade on regional disparity is higher than that of DIEs trade, reflecting the fact that FIEs are predominantly labor-intensive. Our findings are robust and unaffected by the type of trade disaggregation or the econometric techniques used (i.e., FGLS and PCSE). However, the results for the three regions differ depending on the type of trade disaggregation. To achieve the goal of economic development and closing the regional consumption gap, the government must pay close attention to the distribution effects of FIEs and DIEs trade separately and implement a set of measures to reinforce its strengths and mitigate its weaknesses.